Post-laminectomy Dorsal Cord Migration Resulting in Immediate Neurologic Deterioration during Ventral Meningioma Resection: Proposed Mechanism of Injury and Prevention Technique - Harel, Ran; Kimchi, Gil; Perry, Avital; Korn, Akiva; Knoller, Nachshon (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Ventral thoracic meningiomas may pose a technical challenge owing to a limited surgical corridor and the presence of long-standing ventral cord compression. Unopposed dorsal spinal cord migration may occur following a laminectomy resulting in immediate neurologic injury. We discuss the possible mechanism underlying such a phenomenon, suggesting alternative approach to prevent neurologic injury.Methods Two patients operated on for ventral thoracic meningioma and sustained neurologic compromise were retrospectively evaluated. Image editing software was used for 3D modeling to simulate the possible underlying mechanism of injury. Cases where ventral thoracic meningiomas were approached via unilateral hemilaminectomy, performed in 2020, were retrospectively analyzed and compared with the laminectomy approach cohort.Results Two patients sustained postoperative neurologic function decline following resection of ventral thoracic meningioma via the laminectomy approach. Both exhibited permanent abolishment of transcranial motor evoked potentials (MEPs) following laminectomy. Based on the extrapolated 3D models for these two cases, dorsal cord migration was postulated as the cause for the acute neurologic compromise.Conclusion Laminectomy for resection of thoracic ventral meningioma may lead in some cases to dorsal cord migration resulting in grave neurologic deterioration. Unilateral approach to these tumors restricts the dorsal migration and may mitigate neurologic outcomes.
Keywords: thoracic meningioma; dorsal cord migration; unilateral approach; Intradural tumors; Intraoperative neuromonitoring